Boundary coverage and coverage boundary problems in wireless sensor networks. (12th April 2007) - Watfa, Mohamed K.; Commuri, Sesh
The extent of coverage of a Wireless Sensor Network (WSN) is of fundamental importance and determines the utility and effectiveness of the deployment. Determining the least number of sensors required to cover the boundary of a region (boundary coverage) as well as determining the boundary of the sensor cover (coverage boundary) are required for a variety of applications. In this paper, these problems are rigorously analysed and computationally simple algorithms are developed for their distributed implementation. The 'Coverage Hole' problem in sensor networks is also analysed and a distributed algorithm is developed that can identify the boundary of the holes in the sensor cover. Numerical simulations show that the reduced boundary cover has better energy efficiency compared to the standard Random Deployment (RD) of sensor nodes in terms of the overall system lifetime. The proposed algorithms are easy to implement and their computational efficiency is validated through complexity analysis.